Given "y_1(x) = x" and differential equation is "xy'' \u2212 xy' + y = 0" .
Now, "xy_1''-xy_1'+y_1 = x(0)-x(1)+x = 0 - x+x = 0"
Hence, "y_1(x)=x" is solution of given differential equation.
Let the another solution is "y_2(x)" .
we can write a second solution as:
"y_2=cy_1\u222b\\frac{e^{\u222bP(x)dx}} {y_1^2}" where "P(x) = \\frac{-x}{x} = -1" .
Hence, "y_2 = cx \\int \\frac{e^{-x}}{x^2}dx" .
The closed form solution for this is ugly, so we are going to resort to a series solution.
A series solution is given by "y_2(x) ="
"cx\u00d7series \\ expanssion \\ of \\ (\\frac{e^{\u2212x}}{x^2})=cx(\\frac{1}{x^2}\u2212\\frac{1}{x}+\\frac{1}{2}\u2212\\frac{x}{6}+\\frac{x^2}{24}\u2212\\frac{x^3}{120}+O(x4))" .
So. Correct option is option E = "(0,\\infin)" .
Comments
Leave a comment